Jan Paweł II a fenomen objawień maryjnych Królowej Pokoju z Medziugorja = John Paul II and the phenomenon of the Marian apparitions of the Queen of Peace of Medjugorje - Baron, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This study will show the connections between John Paul II and the phenomenon of the apparitions of Our Lady of Medjugorje. The research is based on the analysis of private correspondence of John Paul II with the Skwarnicki family, statements made by the Polish Pope, literature devoted to the events of Medjugorje and their participants as well as the content of the prophecy delivered by the Queen of Peace. On the basis of the aforementioned sources an evaluation of the level of John Paul II`s knowledge, his attitude and private opinions regarding the events taking place in Medjugorje will be carried out.
Keywords: Jan Paweł II, papież (1929-2005); Medjugorje; objawienia maryjne